Ultrastructure of the midgut in Heteroptera (Hemiptera) with different feeding habits - Santos, Helen Pinto; Rost-Roszkowska, Magdalena; Vilimova, Jitka; Serrão, José Eduardo (Protoplasma, 2017)
Heteroptera have diverse feeding habits with phytophagous, zoophagous, and haematophagous species. This dietary diversity associated with the monophyly of Heteroptera makes these insects a good object for comparative studies of the digestive tract. This work compares the ultrastructure of the middle midgut region in the phytophagous Coptosoma scutellatum (Plataspidae), Graphosoma lineatum (Pentatomidae), Kleidocerys resedae (Lygaeidae), and zoophagous Rhynocoris iracundus (Reduviidae), Nabis rugosus (Nabidae), and Himacerus apterus (Nabidae), to verify if diet affects midgut cells in phylogenetically related insects. The middle region of the midgut was used for comparison because it is the main site for digestion and absorption of the midgut. The digestive cell ultrastructure was similar in the six species, with features of secretory, absorptive, transport, storage, and excretory cells, suggesting a stronger correlation of middle digestive cell ultrastructure with the phylogeny of these species than with the different heteropteran feeding habits.
Keywords: gastrointestinální trakt; Carnivory; Basal labyrinth; Heteroptera; Animals; Gastrointestinal Tract; Herbivory; Digestive cells; zvířata; Zoophagy; Regeneration; Phytophagy; Comparative morphology; regenerace; Regenerative cells; Spherocrystals; masožravci; býložravci